2002
DOI: 10.1046/j.1365-2168.2002.02277.x
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical studies of gene transfer for the treatment of desmoid disease in familial adenomatous polyposis

Abstract: Liposomal transfection of APC gave prolonged high-level expression of the transgene, an important basis for gene therapy. No adverse effects were recorded. Further work is needed in animal models of desmoid disease to assess the clinical effects of gene therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0
1

Year Published

2004
2004
2009
2009

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 36 publications
0
14
0
1
Order By: Relevance
“…Medical therapy including NSAID, sulindac, chemotherapy including doxorubicin, radiotherapy and antiestrogen therapy with tamoxifen may be used in case of inoperable tumours [6,[13][14][15][16][17][18]. A possible future therapy is gene therapy by reintroduction of the APC gene into human fibroblasts [19]. Our patient was only 17 years old and presented with severe abdominal pain lasting for 4 days.…”
Section: Discussionmentioning
confidence: 96%
“…Medical therapy including NSAID, sulindac, chemotherapy including doxorubicin, radiotherapy and antiestrogen therapy with tamoxifen may be used in case of inoperable tumours [6,[13][14][15][16][17][18]. A possible future therapy is gene therapy by reintroduction of the APC gene into human fibroblasts [19]. Our patient was only 17 years old and presented with severe abdominal pain lasting for 4 days.…”
Section: Discussionmentioning
confidence: 96%
“…9 This occurred at the same time as investigators sought to prevent the onset of duodenal cancer by a range of prophylactic measures, which have had drug, endoscopic, or surgical components, 1 5-8 with the promise of gene therapy to come. [10][11][12] Underpinning these attempts to improve outcome was the development of the duodenal staging system now used by several groups. [6][7][8] Despite being the subject of some cynicism initially, the staging system described appears to be useful in determining the frequency of endoscopic examination of the upper gastrointestinal tract as well as in delineating the core group of patients at very high risk for duodenal cancer and for whom preventative measures are most urgent.…”
mentioning
confidence: 99%
“…[3][4][5][6][7][8][9][10][11] Many studies have reported on the improvement of the transfection efficiency as a result of the development of synthetic cationic liposome. [3][4][5][6][7][8][9][10][11] These studies were significant in the investigations of gene function [12][13][14][15][16][17][18] and gene therapy [19][20][21][22][23][24][25][26][27][28][29][30] in a broad range of diseases; the processes are safe, simple, and non-immunogenic.…”
Section: Introductionmentioning
confidence: 99%
“…Among various kinds of liposomes, cationic ones are efficient in gene transfer because they can strongly interact with DNAs and can spontaneously form cationic liposome-DNA complexes. They fuse the plasma membrane of cells and facilitate the delivery of functional DNA into the nucleus at high probability.3-11 Many studies have reported on the improvement of the transfection efficiency as a result of the development of synthetic cationic liposome.3-11 These studies were significant in the investigations of gene function 12-18 and gene therapy [19][20][21][22][23][24][25][26][27][28][29][30] in a broad range of diseases; the processes are safe, simple, and non-immunogenic.A number of studies of DNA, cationic liposomes, and their complexes at solid/liquid, air/liquid, and liquid/liquid interfaces have been conducted to investigate the structures and properties of DNA-surfactant complexes at interfaces using UV-visible spectrophotometry, The dynamic behaviors of cationic liposome-DNA complexes in inside and outside biomembrane models upon lipofection were investigated using the time-resolved quasi-elastic laser scattering (QELS) method. Inside and outside biomembrane models with similar phospholipid compositions to those in living cells were formed at a tetradecane/phosphate buffered saline (TD/PBS) interface.…”
mentioning
confidence: 99%
See 1 more Smart Citation